1999
DOI: 10.1161/01.hyp.34.3.408
|View full text |Cite
|
Sign up to set email alerts
|

Role of Angiotensin Receptor Subtypes in Mesenteric Vascular Proliferation and Hypertrophy

Abstract: Abstract-The aim of this study was to explore the regulation of angiotensin receptors after chronic infusion with angiotensin II (Ang II) and to clarify the relative roles of the angiotensin type 1 (AT 1 ) and type 2 (AT 2 ) receptors in the mediation of Ang II-induced mesenteric vascular hypertrophy. In male Sprague-Dawley rats, Ang II infusion at a dose of 58.3 ng/min by subcutaneous osmotic minipumps for 14 days led to increased mesenteric weight and wall:lumen ratio of the vessels and proliferation of smoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 38 publications
(47 reference statements)
5
54
0
Order By: Relevance
“…AT1 receptor mRNA is also increased in ROP and this finding, together with our previous report that AT1-RB reduces retinal angiogenesis in ROP, 7 is consistent with AT1 and AT2 receptors having similar pro-angiogenic roles in ROP. A trophic action for both the AT1 and AT2 receptors in the retina is consistent with reports that AT1-RB and AT2-RB are anti-proliferative in proximal tubules, 16 the mesenteric arterial tree, 32 and mouse spleen lymphocytes. 41 There is also evidence that the AT2 receptor promotes cell growth and inflammation in vascular smooth muscle cells, rat embryo, and cultured cells.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…AT1 receptor mRNA is also increased in ROP and this finding, together with our previous report that AT1-RB reduces retinal angiogenesis in ROP, 7 is consistent with AT1 and AT2 receptors having similar pro-angiogenic roles in ROP. A trophic action for both the AT1 and AT2 receptors in the retina is consistent with reports that AT1-RB and AT2-RB are anti-proliferative in proximal tubules, 16 the mesenteric arterial tree, 32 and mouse spleen lymphocytes. 41 There is also evidence that the AT2 receptor promotes cell growth and inflammation in vascular smooth muscle cells, rat embryo, and cultured cells.…”
Section: Discussionsupporting
confidence: 91%
“…Our group has previously reported that PD123319 requires continuous administration to effectively block the AT2 receptor in blood vessels and kidney using in vitro and in vivo autoradiography techniques. 16,32 By contrast, the daily administration of a single subcutaneous dose of PD123319 by Lonchampt and colleagues 40 which failed to confer retinal protection was not clearly demonstrated by that group to block the AT2 receptor in vivo. However, it must be acknowledged that the abundance of AT1 and AT2 receptors in the mouse and rat retina may also account for the discrepancies between the studies.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…19,20 However, it has also been shown that the AT2 receptor acts in concordance with the AT1 receptor in collagen synthesis in cultured vascular smooth muscle cells, 21 in proliferative effects in mesenteric artery, 22 and in smooth muscle cell growth and extracellular matrix expression in the aorta. 23 In adrenal tissues, both the AT2 receptor and the AT1 receptor are thought to stimulate aldosterone secretion.…”
Section: Discussionmentioning
confidence: 99%
“…This study and several others that suggest either prohypertrophic or antihypertrophic effects of AT 2 are summarized in the Table. 7,[25][26][27][28][29][30] The fact that growth-promoting effects of AT 2 were not observed in earlier in vitro studies is not surprising, because AT 2 disappears rapidly in ordinary cell culture conditions. 10 However, the in vivo experiments shown in the Table appear to show that AT 2 both suppresses and promotes vascular cell growth, hypertrophy, and fibrosis, and these conflicting results are more difficult to explain.…”
Section: Involvement Of At 2 In Cardiovascular Hypertrophy-associatedmentioning
confidence: 96%